PENGARUH TANGGUNG JAWAB MORAL, SANKSI PERPAJAKAN DAN PENERAPAN SISTEM E-FILING PADA KEPATUHAN PELAPORAN WAJIB PAJAK - Inten Yulitasari, Anak Agung; Suprasto, Herkulanus Bambang (E-Jurnal Akuntansi, 2017)
Tax is the largest contributor to the State's revenue in financing national development. One way that can be done so that national income can increase, namely by improving compliance reporting that is currently still considered less. The purpose of this study to determine the effect of moral responsibility, tax sanctions and application of E-Filing system on compliance reporting Individual Taxpayers in the Tax Office Primary East Denpasar. The method used in this research is non probability sampling with purposive sampling technique. The type of data used in this study is quantitative and qualitative data. Population used in this research is Personal Taxpayer registered and classified as Taxpayer Effective in Tax Office Primary East Denpasar. Methods of data collection through questionnaires that have been distributed to 100 respondents who have met the criteria and data published through the website or from the Tax Office Primary East Denpasar and then the data were analyzed using multiple linear regression analysis techniques. The results of testing in this study indicate that moral responsibility has a positive effect on compliance reporting of Individual Taxpayer. Tax sanctions have a positive effect on the compliance of Personal Taxpayer reporting. Implementation of E-Filing system has a positive effect on compliance reporting of Individual Taxpayer at Tax Office Primary East Denpasar.